Bioterios - Gómez-García, José Pablo (Instituto Tecnológico de Costa Rica., 2010)
Major advances in knowledge of biomedical research have been achieved by animal testing. Quality and validity of such assays is subject to standardization of individuals used for testing. On the face of these facts, on a national and international level, regulations on facilities and research protocols have been proposed, considering both scientific needs and animal welfare. Part of the measures which pretend to assure suitability of the animals destined to biomedical assays, consists on controlling the environmental quality of the breeding spaces, and such, compliance with regulations in the planning of architectural design of these type of facilities becomes essential. Being environmental and sanitary controls a priority in spaces where animals destined to research are confined, human comfort in these áreas becomes limited by the environmental needs of the species of work interest, so special attention is paid on the space quality of exterior support facilities, with the objective of perceptually offset the controlled environment spaces. This graduation project brings a proposal based on the appliance of parameters, regulations and needs of a breeding facility for conventional animals (i.e. rats and mices), which are destined to research purposes in an animal housing model which takes in consideration both animal standarization needs and human comfort in areas where this can be allowed.
instalaciones para la cría de animales convencionales de laboratorio
Proyecto de graduación (Licenciatura en Arquitectura y Urbanismo) Instituto Tecnológico de Costa Rica, Escuela de Arquitectura y Urbanismo, 2010.
Keywords: Arquitectura; Animales; Experimentos; Construcción; Diseño arquitectónico; Bioterios; Diseño urbano